Current status and key factors for coalbed methane development with multibranched horizontal wells in the southern Qinshui basin of China. Issue 5 (27th May 2019) - Chen, Shida; Tang, Dazhen; Tao, Shu; Yang, Yanhui; Chen, Longwei
Abstract: The Qinshui basin is the most successful area for coalbed methane (CBM) development in China. Since 2008, 45 multibranched horizontal wells (MBHWs) have been put into production in the Fanzhuang block, of which 10 wells have an average daily gas rate (DGR) of >10 000 m 3 /d. Well 4‐5 with the total gas production of 1.054 × 10 8  m 3 achieved the China's highest DGR of 63 744 m 3 /d. Compared with vertical wells, MBHW is an effective way to develop CBM in low permeability reservoirs in China. However, there are still 23 wells have an average DGR of <3000 m 3 /d, of which 18 wells are below 1000 m 3 /d. The results show that shallow depth (<600 m), high gas content (>16 m 3 /t) and saturation (>80%), long coal seam interval (>3000 m), reasonable branch spread, and stable wellbore are the basis for achieving high production. The encountered faults connected to the aquifer will cause a high water production and an extremely low gas rate (<1000 m 3 /d). In the inclined coal seam, the up‐dip MBHW is more favorable for the formation water drainage and the pressure drop funnel expansion than the down‐dip MBHW, and the horizontal well should be drilled perpendicular to the high‐permeability direction to achieve a higher recovery ratio. MBHW is more sensitivity to drainage rate due to the coal fine migration in the horizontal segments, and the high pressure drop rate will lead to high frequency of stunk pump and eventually affect the gas production. Currently, the biggest challenge for CBM development with MBHW is wellbore stability. 57% of inefficient wells are caused by wellbore collapse during drilling and production processes. Here, a new type of "Roof Drilling‐Tree Shaped" horizontal well structure was presented in this work. The first "Roof Drilling‐Tree Shaped" horizontal well with a total length of 12 288 m and a coal seam interval of 9408 m was successfully applied without drilling accidents. Abstract : After more than 20 years of exploration and development, by the end of 2017, China has drilled 17 800 CBM wells, including 16 219 production wells with an annual gas production of 49.59 × 10 8  m 3 . However, the average daily CBM production in China is only 838 m 3 /d per well, far lower than other countries. Except for complex geological conditions, the single development mode is also an important reason that cannot be ignored. Vertical wells with artificial fracturing technology account to 98% of CBM wells in China, while the number of horizontal wells is only about 400. Exploring more adaptive and diverse development technologies is critical to the CBM commercial development plans.